TRENDS OF HUMAN RESOURCE DEVELOPMENT IN HEALTH CARE OF WHO MEMBER STATES - Leshchenko V.V. (Pressing Problems of Public Administration, 2016)
Trends of human resources for health development in the WHO member states have been examined.WHO Global Health Observatory data on global health workforce and based on the needs healthworkers’ shortfall have been analyzed. The need for active government intervention to address theseproblems has been indicated.